P. RAMLEE: LEGENDA YANG TERUS HIDUP - Aimi Jarr 1939-2011 (Kuala Lumpur : VARIAPOP GROUP, 1999)
Menyingkap kisah-kisah yang belum pernah diketahui umum.
Keywords: P. Ramlee, -- Tan Sri, -- 1929-1973; Actors, Malay -- Biography; Musicians -- Biography -- Malaysia